Let-7b overexpression leads to increased radiosensitivity of uveal melanoma cells. Issue 2 (April 2015) - Zhou, Yixiong; Zhang, Leilei; Fan, Jiayan; Jia, Renbin; Song, Xin; Xu, Xiaofang; Dai, Liyan; Zhuang, Ai; Ge, Shengfang; Fan, Xianqun
Abstract : Uveal melanoma (UM) is an intraocular malignant tumor in adults that is characterized by rapid progression and recurrence. Irradiation has become the primary therapy for UM patients who are not candidates for surgery. However, after large-dose fraction irradiation treatment, some patients undergo subsequent enucleation because of radiotherapy-related complications. This situation has raised concerns on how to optimize the effectiveness of radiation treatment. Recent investigations of microRNAs are changing our understanding of UM tumor biology and are helping to identify novel targets for radiotherapy. The radioresistant UM cell lines OM431 and OCM1 were selected and exposed to irradiation, and let-7b was found to be downregulated after exposure. We then confirmed that let-7b mimics could inhibit UM growth both in vitro and in vivo . More specifically, transfection with let-7b mimics markedly resensitized OCM1 and OM431 cells to irradiation by reducing the population of S-phase cells. Cyclin D1 plays a vital role in cell cycle arrest, which is induced by let-7b overexpression. Cyclin D1 is also a target of let-7b and its expression is suppressed by upregulation of let-7b . Collectively, our results indicate that let-7b overexpression can in turn downregulate cyclin D1 expression and enhance the radiosensitivity of UM through cell cycle arrest. Let-7b could serve as a marker for radiosensitivity and could enhance the therapeutic benefit of UM cell irradiation.